Impact of tobacco control policies on adolescent smokeless tobacco and cigar use: a difference-in-differences approach - Summer Sherburne Hawkins; Nicoline Bach; Christopher F. Baum (BMC, 2018)
Abstract Background While increasing cigarette taxes has been a major policy driver to decrease smoking, taxes on other tobacco products have received less attention. Our aims were to evaluate the impact of chewing tobacco/cigar taxes, cigarette taxes, and smoke-free legislation on adolescent male and female use of smokeless tobacco and cigars. Methods We analyzed data on 499,381 adolescents age 14-18 years from 36 US states in the Youth Risk Behavior Surveys (1999-2013) linked to state-level tobacco control policies. We conducted difference-in-differences regression models to assess whether changes in taxes and the enactment of smoke-free legislation were associated with smokeless tobacco use and, separately, cigar use. Models were stratified by adolescent sex. Results We found that chewing tobacco taxes had no effect on smokeless tobacco use and cigar taxes had no effect on cigar use. In contrast, among males a 10% increase in cigarette taxes was associated with a 1.0 percentage point increase (0.0010, 95% CI 0.0003-0.0017) in smokeless tobacco use. A 10% increase in cigarette taxes was also associated with a 1.5 percentage point increase (0.0015, 95% CI 0.0006-0.0024) in cigar use among males and a 0.7 percentage point increase (0.0007, 95% CI 0.0001-0.0013) in cigar use among females. There was some evidence that smoke-free legislation was associated with an 1.1 percentage point increase (0.0105, 95% CI 0.0015-0.0194) in smokeless tobacco use among males only, but no effect of smoke-free legislation on cigar use for males or females. Conclusions Higher state cigarette taxes are associated with adolescents' use of cheaper, alternative tobacco products such as smokeless tobacco and cigars. Reducing tobacco use will require comprehensive tobacco control policies that are applied equally to and inclusive of all tobacco products.